The Determines of Loan Loss Provision in the US Banking Industry from 2012 to 2018 - JIANG, Liyan (2019)
In this paper, it is mainly discussed loan loss provision decisions for 230 commercial banks in the US banking industry during the year from 2012 to 2018. The paper uses the Stochastic Frontier Approach (SFA) to measure cost efficiency and use the Generalized Method of Moments (GMM) to analyze. The main data come from Orbis and the World Bank. By reading different literature, it assumes that income smoothing, earning management, capital management, Basel Accords, business cycle, and other hypotheses have a correlation with loan loss provision behavior. The empirical results show that business cycle, earning management, capital management and size have a significant correlation with loan loss provision. However, there is no evidence for cost efficiency and Basel Accords in the US commercial banks. To sum up, the results are mixed. There are some reasons and further suggestions given at last. Keywords: Loan loss provision; Earning management; Income smoothing, Capital management, Business cycle, Cost Efficiency, SFA, GMM